Prevalence and Predictors of Neurocognitive Impairment in Ethiopian Population Living with HIV - Salahuddin M (Dove Medical Press, 2020)
Mohammed Salahuddin,1,2 Md Dilshad Manzar,3 Hamid Yimam Hassen,4,5 Aleem Unissa,6 Unaise Abdul Hameed,7 David Warren Spence,8 Seithikurippu R Pandi-Perumal9 1Department of Pharmacy, College of Medicine and Health Sciences, Mizan-Tepi University (Mizan Campus), Mizan, Ethiopia; 2Pharmacology Division, Department of BioMolecular Sciences, University of Mississippi, Oxford, Mississippi, USA; 3Department of Nursing, College of Applied Medical Sciences, Majmaah University, Al Majmaah 11952, Saudi Arabia; 4Department of Public Health, College of Health Sciences, Mizan Tepi University, (Mizan Campus), Mizan, Ethiopia; 5Department of Primary and Interdisciplinary Care, College of Medicine and Health Sciences, University of Antwerp, Antwerp, Belgium; 6Malla Reddy College of Pharmacy, Hyderabad, Telangana, India; 7Department of Physiotherapy, Faculty of Medicine, Nursing and Health Sciences, Monash University, Australia; 8Independent Researcher, Toronto, ON M6K 2B4, Canada; 9Somnogen Canada Inc, Toronto, ON, CanadaCorrespondence: Mohammed Salahuddin Department of BioMolecular SciencesUniversity of Mississippi, School of Pharmacy, 331 Faser Hall, P.O. Box 1848, University, MS 38677-1848 Tel +1 662-609-3011Email smohamme@go.olemiss.eduBackground: Modern antiretroviral therapy has extended the life expectancies of people living with HIV; however, the prevention and treatment of their associated neurocognitive decline have remained a challenge. Consequently, it is desirable to investigate the prevalence and predictors of neurocognitive impairment to help in targeted screening and disease prevention.Materials and Methods: Two hundred and forty-four people living with HIV were interviewed in a study using a cross-sectional design and the International HIV Dementia Scale (IHDS). Additionally, the sociodemographic, clinical, and psychosocial characteristics of the patients were recorded. Chi-square and binary logistic regression analysis were used to determine the level of significance among the independent risk factors and probable neurocognitive impairment.Results: The point prevalence of neurocognitive impairment was found to be 39.3%. Participants’ characteristics of being older than 40 years (AOR= 2.81 (95% CI; 1.11– 7.15)), having a history of recreational drug use (AOR= 13.67 (95% CI; 6.42– 29.13)), and being non-compliant with prescribed medications (AOR= 2.99 (95% CI; 1.01– 8.87)) were independent risk factors for neurocognitive impairment.Conclusion: The identification of predictors, in the Ethiopian people living with HIV, may help in the targeted screening of vulnerable groups during cART follow-up visits. This may greatly help in strategizing and implementation of the prevention program, more so, because (i) HIV-associated neurocognitive impairment is an asymptomatic condition for considerable durations, and (ii) clinical trials on neurocognitive impairment therapies have been unsuccessful.Keywords: cART, HIV, IHDS, Africa, dementia, Ethiopia, recreational drugs